دورالتّرجمة في إرساء التّقارب المجتمعيّ: ترجمة مواقع ويب الفنادق كأداة استراتيجية للترويج الفعال عبر الثقافات: The Role of Translation in establishing Community Rapprochement: Translating Hotels Website as A Strategic Tool for Effective Cross-Cultural Promotion - Mammad , Tawfik; Boutchacha, Djamel (Maalim, 2023)
The impetus behind the present paper is to highlight the role of translation in sustaining cultural rapprochement through multilingualism in the service of Algeria's tourism sector. It sheds light on the way electronic web sites of Algerian hotels are being translated. The paper deals with the importance of translation in approaching communities and aim to introduce the importance of web translation in the promotion of tourism and in the development of the economy. A sample of web pages of El-Djazair hotel were analyzed, commenting on its translations into English and French, and on the adaptation and localization strategies being employed, drawing heavily on translation and localization theories.